Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT. Medion Ardhika Bhakti Kab. Bandung Barat - Nurjamad, Moh Aep; Purnama, Nanda (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The aim of this research is to determine the influence of work motivation and work discipline on employee performance at PT Medion Ardhika Bhakti, both partially and simultaneously. This research uses descriptive and associative research methods. The population in this study was 208 and the sample taken for this research was 137 respondents. The sampling technique used in this research is probability sampling technique, simple random sampling. The research instrument used in this research was a questionnaire distributed to respondents with data analysis using linear regression. Based on the research results, it can be concluded that work motivation has a positive and significant effect on the performance of PT Medion Ardhika Bhakti employees and work discipline has a positive and significant effect on the performance of PT Medion Ardhika Bhakti employees. Simultaneously, work motivation and work discipline have a positive and significant effect on performance.